2016
DOI: 10.3389/fsurg.2016.00038
|View full text |Cite
|
Sign up to set email alerts
|

The Split Second Effect: The Mechanism of How Equinus Can Damage the Human Foot and Ankle

Abstract: We are currently in the process of discovering that many, if not the majority, of the non-traumatic acquired adult foot and ankle problems are caused by a singular etiology: non-neuromuscular equinus or the isolated gastrocnemius contracture. There is no question that this biomechanical association exists and in time much more will be uncovered. There are three basic questions that must be answered: why would our calves tighten as we normally age, how does a tight calf, or equinus, actually cause problems remo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 65 publications
1
11
0
Order By: Relevance
“…Just before the heel-off phase, damaging forces are produced where both direct and indirect forces are created and magnified by the tightness of calf muscles restricting the tibial translation over the ankle joint. 57 The tightness of calf muscles could also result in altered kinematics at the ankle such as decreased ankle dorsiflexion at terminal midstance and toe-off (,108), as seen in the present study (Table 4).…”
Section: Motor Neuropathysupporting
confidence: 55%
See 1 more Smart Citation
“…Just before the heel-off phase, damaging forces are produced where both direct and indirect forces are created and magnified by the tightness of calf muscles restricting the tibial translation over the ankle joint. 57 The tightness of calf muscles could also result in altered kinematics at the ankle such as decreased ankle dorsiflexion at terminal midstance and toe-off (,108), as seen in the present study (Table 4).…”
Section: Motor Neuropathysupporting
confidence: 55%
“…56 The association of calf muscle (gastrocnemius and soleus) tightness with kinetics and kinematics of the foot could be well explained by the split second effect suggested by a study. 57 The study suggested that there were two types of forces (direct and indirect) created by the split second effect over a critical period of 120 msec during terminal midstance. Just before the heel-off phase, damaging forces are produced where both direct and indirect forces are created and magnified by the tightness of calf muscles restricting the tibial translation over the ankle joint.…”
Section: Motor Neuropathymentioning
confidence: 99%
“…Damaging forces appear when leveraged forces are transmitted to the foot and ankle as the tibia (and the body) passes over the planted foot. 24 Shortening of the gastrocnemius, congenital or acquired, is the most common cause of the lack of ankle joint dorsiflexion. During the late part of the second rocker of gait (just before heel lift) ankle dorsiflexion should be coupled with full knee extension.…”
Section: Pathomechanicsmentioning
confidence: 99%
“…An increased mechanical load due to a higher BMI seems a very plausible source of increased plantar fascial stress (46), and the association between the BMI and musculoskeletal symptoms in general is widely recognized (59). A tight or contracted Achilles tendon is also thought to produce greater tensile loads in the fascia through direct transmission of tension through the calcaneal trabecular system, as proposed by Arandes and Viladot (60) and/or by increasing its passive mechanical longitudinal tension as a method of counteracting the arch flattening effect of ankle dorsiflexion stiffness (61,62).…”
Section: Biomechanics Of Plantar Fasciitismentioning
confidence: 99%